The Impact of Artificial Intelligence on Educational Transformation: Trends and Future Directions - Khatun, Maimuna; Islam, Rafia; Kumar, Sobuz; Hossain, Rashed; Mani, Lisa (Journal of Information System and Informatics, 2024)
This study conducts a systematic review using the PRISMA framework to explore the intersection between escalation profounder perceptions and appreciative into AI technology interconnected education. The novelty of this research lies in its synthesis of AIEd research, highpoints designated AIEd technologies and applications, evaluations the proven and potential benefits for education, connections the gaps between AI technological innovations and educational applications and generates practical illustrations and inspirations for both technological experts that create AIEd technologies and educators who spearhead AI innovations in education. Using a PRISMA-based approach, this review systematically analyzed 175 articles across multiple databases being journal articles or full conference papers and a method section publications were included for data extraction and synthesis, focusing on AI's influence on personalized learning. This systematic review presents a comprehensive synthesis of recent scientific findings concerning the disruptive effects of artificial intelligence on the educational sector. Key findings reveal that AI enhances learning efficiency but raises ethical concerns regarding privacy and bias. Limitations include the variability of AI tools in different educational settings and the need for longitudinal studies to assess long-term impact. However, some risks are associated with artificial intelligence advancements such as safety, security, and privacy concerns. As a result, artificial intelligence technologies positively and negatively affect the education sector. Future of the study explores VR, AR, and MR being embraced with AI for learning tools, interdisciplinary and transdisciplinary research which is effective expansion revision of AI in education. Thus, AI in education approaches to encounter desires and potentials through AI technologies which will be excellent by the aware of trends in AIEd applications and future directions.